Effectiveness Extract of Noni Leaf (Morinda citrifolia L.) and Bintaro Leaf (Cerbera odollam) Against Mortality of Spodoptera litura F. - Luqman, Bay Andi; Yuliani, Yuliani (LenteraBio : Berkala Ilmiah Biologi, 2023)
Spodoptera litura is a polyphagous pest that has a wide host range and can reduce yields up to 80% on soybeans. Farmers control it with synthetic pesticides, but in the long term, it can cause environmental pollution and pest resistance. Therefore, an environmentally friendly alternative is needed, such as using plant-based pesticides. The content in the leaves of M. citrifolia and C. odollam are saponins, flavonoids, tannins, and cerberin which are active ingredients that have the potential to become vegetable pesticides. This study aims to determine the effect of leaf extract types M. citrifoli, C. odollam and their combinations, extract concentration, and the interaction between extract types and concentrations on mortality of S. litura F. This study used two experimental RAL factors, namely the type of leaf extract of M. citrifolia, C. odollam and their combinations and the type of concentration, namely 0%, 1%, 2%, 3%, 4%, and 5% with five repetitions, so there were 30 units. . Data analysis using two-way ANOVA continued with Duncan's test. The results showed that there was an effect of the type of leaf extract of M. citrifoli, C. odollam, and their combination and the type of concentration on the mortality of caterpillars. But there is no interaction between the type of extract and concentration. The mortality of caterpillars was directly proportional to the high concentration of the extract. The type of extract combination of M. citrifolia and C. odollam and a concentration of 5% was the best type of extract and the concentration because it resulted in a mortality of S. Litura F of 75.40%.